Cracks width-corrosion rate correlation on the durability of reinforced concrete in a very high aggressiveness tropical marine environment - Torres Acosta, Andrés Antonio; Troconis de Rincón, Oladis; Milano, Valentina; Hernández-López, Yolanda (Revista ALCONPAT, 2018)
The aim of this investigation was evaluate the correlation between crack width and apparent corrosion rate in reinforced concrete specimens exposed for more than six years to a tropical marine environment, at the natural test site La Voz, Venezuela. Six specimens from DURACON Project (prismatic 15x15x60 cm, with 0.65 w/c ratio) were monitored; each specimen having six reinforcing steel bars placed at three different depths (two each at 15, 20, and 30 mm) for electrochemical tests (corrosion potential and corrosion rate). An empirical correlation between surface crack propagation rate and iCORR was established, which may help iCORR estimation indirectly if values of maximum surface crack widths due to reinforcement corrosion are obtained in at least one year period of monitoring.